Relationship between percentage of body fat and anthropometric indicators in individuals attending a gym - T. Grossl; L.R. Augustemak De Lima; F.C. Karasiak (Desafio Singular, 2010)
The aim of this study was to investigate the relationship between percentage of body fat (% BF) and anthropometric indicators in individuals attending a gym. Four hundred and thirty eight individuals, 195 men and 243 women, from 18 to 50 years of age took part in this study. The % BF was estimated by the skinfold method. The following anthropometric indicators were assessed: waist circumference, abdomen circumference (AC), waist-to-hip ratio, body mass index (BMI) and waist-height ratio. Linear Pearson correlation and simple linear regression analysis were used to investigate the relationship between variables. For women, BMI strongly correlated with % BF (r = .73), whereas for males, AC showed high correlation with % BF (r = .73). With varying degrees of magnitude, there were significant correlations between all of the anthropometric indicators analyzed and % BF.